2012
DOI: 10.1002/arch.21050
|View full text |Cite
|
Sign up to set email alerts
|

SILKWORM 30K PROTEIN INHIBITS ECDYSONE‐INDUCED APOPTOSIS BY BLOCKING THE BINDING OF ULTRASPIRACLE TO ECDYSONE RECEPTOR‐B1 IN CULTURED Bm5 CELLS

Abstract: This study investigates the mechanism through which increased 30K protein inhibits ecdysone-induced apoptosis in the Bm5 silkworm ovarian cell line. Treatment of Bm5 cells with 20-hydroxyecdysone (20E) after transfection with the pIZT/V5-His control vector triggered apoptosis, but 20E treatment did not trigger apoptosis in Bm5 cells transfected with the pIZT/30K/V5-His vector. To confirm its inhibitory effect on apoptosis, 30K protein was first purified from Escherichia coli transformed with a 30K expression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This result was an update from a previous analysis based on the newly identified 30K proteins in the UniProt database, as in previous analysis, we only identified 11 acetylated 30K proteins containing 23 Kac sites (Nie et al, ). As members of the lipoprotein family, 30K proteins mainly perform the lipid loading (J. P. Yang et al, ) and antiapoptosis functions (E. J. Kim et al, ; E. J. Kim, Rhee, & Park, ; M. Y. Kim et al, ; Pakkianathan et al, ; Yu et al, ). The widespread acetylation of B. mori 30K proteins might suggest important roles of acetylation with respect to the function of 30K proteins in silkworms, which requires additional studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was an update from a previous analysis based on the newly identified 30K proteins in the UniProt database, as in previous analysis, we only identified 11 acetylated 30K proteins containing 23 Kac sites (Nie et al, ). As members of the lipoprotein family, 30K proteins mainly perform the lipid loading (J. P. Yang et al, ) and antiapoptosis functions (E. J. Kim et al, ; E. J. Kim, Rhee, & Park, ; M. Y. Kim et al, ; Pakkianathan et al, ; Yu et al, ). The widespread acetylation of B. mori 30K proteins might suggest important roles of acetylation with respect to the function of 30K proteins in silkworms, which requires additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…J. Kim, Rhee, & Park, 2001; M. Y. Kim et al, 2012;Pakkianathan et al, 2015;Yu et al, 2013). The widespread acetylation of B. mori 30K proteins might suggest important roles of acetylation with respect to the function of 30K proteins in silkworms, which requires additional studies.…”
Section: Acetylation Profiles Of 30k Proteins In B Morimentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, 30K proteins have been shown to play a role in antiapoptosis (Kim et al ., , , ; Kim & Park, ; Choi et al ., ; Song et al ., ). At the PP stage and on PP1, genomic DNA is gradually concentrated in SG, and it is rapidly and completely degraded on PP1 according to the DNA ladder.…”
Section: Discussionmentioning
confidence: 98%
“…30Kc6 protein inhibits apoptosis in human and insect cells (Kim et al ., ; Kim & Park, ; Choi et al ., ). It is gradually synthesized in the Bombyx motorneurones and results in inhibition of programmed cell death in vitro by blocking ultraspiracle binding to ecdysone receptor‐B1 (EcR‐B1) through the formation of a 30K/EcR‐B1 complex (Kim et al ., ; Song et al ., ). 30Kc19 is not only an apoptosis‐inhibiting factor but also perhaps a proteinaceous factor involved in the uptake of the chymotrypsin inhibitor (CI‐8) into the midgut through the membrane (Kim et al ., ; Ueno et al ., ).…”
Section: Introductionmentioning
confidence: 98%